PELATIHAN BINA USAHA MEMBUKA BENGKEL SEPEDA MOTOR UNTUK PEMUDA KELURAHAN BUKIT DATUK - Arif, Muhammad; Faisal, Rudi; John Suarlin (Komunitas Manajemen Kompetitif, 2025)
Entrepreneurs are people who carry out entrepreneurial activities characterized by being good at seeing opportunities and talented at recognizing new services or products, determining how to do business, compiling business needs, being able to carry out operational management. Currently, a business that provides an open opportunity to be used as an initial business for young people is opening a motorcycle repair shop. The motorcycle repair service business is a small business that is run for the first step of doing business in increasing income for daily living needs. Empowering male teenagers to open a business as a form of new entrepreneurship is needed with the aim of increasing the income of people engaged in small-scale business activities, especially in order to obtain additional income. The method of implementing activities is carried out with an approach that prioritizes the results of joint formulation according to the needs in organizing the empowerment program being carried out. This activity produces a motorcycle repair business that has the potential to increase the income of these teenagers so that they have entrepreneurial skills and become productive youth.